Sedimentary facies, fossil distribution and depositional setting of the late Ediacaran Tamengo Formation (Brazil). Issue 7 (30th May 2020) - Amorim, Kamilla Borges; Afonso, Jhon Willy Lopes; Leme, Juliana de Moraes; Diniz, Cleber Quidute Clemente; Rivera, Laura Carolina Montenegro; Gómez‐Gutiérrez, Juan Camilo; Boggiani, Paulo César; Trindade, Ricardo Ivan Ferreira
Abstract: Mixed carbonate–siliciclastic deposits of the Tamengo Formation (terminal Ediacaran), record the rise of calcifying metazoans and the origin of exoskeletons in animals. To explore the relationships between environmental setting and the first appearance of calcified metazoans and their ecology, this study presents detailed sedimentological and stratigraphic data of eight sections that capture the final stages of the Ediacaran (550 to 543 Ma). This study combines stratigraphic characterization with detailed facies descriptions and evaluates lateral heterogeneity and overall ramp sedimentation integrated with fossil distribution. The Tamengo Formation represents a storm‐dominated ramp. The outer to mid‐ramp is composed of very fine‐grained siliciclastic rocks containing Corumbella body fossils and thin‐bedded mudstone/wackestone containing Cloudina . The mid‐inner ramp is dominated by wackestone/packstone with abundant Cloudina skeletal debris and ooid packstone/grainstone shoal deposits. Locally, fragments of Corumbella and Cloudina are found on the same horizon, which is a result of their high accumulation rate, resulting from the reworking and mixing of epifaunal organisms. In spite of taphonomic biases, the general distribution of Corumbella and Cloudina across the unit suggests that these organisms have been transported across ramp and/or probably show a differential response of fauna preservation. When compared to other occurrences worldwide, this dataset indicates an already complex ecosystem in the Ediacaran, where these early animals were capable of adapting to specific environmental niches.